2009
DOI: 10.31018/jans.v1i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing seedling production of black velvet tamarind (Dialium guineense Willd) 1

Abstract: The present investigation was conducted to enhance seedling production of Black Velvet Tamarind (Dialium guineense). Three different types (sets) of experiments were designed. The results showed no sprouting of the stem cuttings in the first type of experiment ( stem cuttings treated with Naphthalene Acetic Acid (NAA) and coconut milk). The second type of experiment (seeds subjected to some pre-sowing treatments using NAA, coconut milk, manual scarification and seeds soaked in water for 24 hrs) showed highly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…BVT is an important non-timber multipurpose agroforestry crop with a high potential (Nwaoguala et al, 2007). The potentials of BVT as food supplement, in herbal medicine and as source of energy are well documented by Ogbe and Egharevba (1992), Aghartise and Egharevba (1994), Nwaoguala et al (2007) and Nwaoguala and Osaigbovo (2009). According to Ogbe and Egharevba (1992), BVT is a lesser known tropical forest fruit with high consumption but given a less priority in terms of research, production, improvement, storage and hence not domesticated.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…BVT is an important non-timber multipurpose agroforestry crop with a high potential (Nwaoguala et al, 2007). The potentials of BVT as food supplement, in herbal medicine and as source of energy are well documented by Ogbe and Egharevba (1992), Aghartise and Egharevba (1994), Nwaoguala et al (2007) and Nwaoguala and Osaigbovo (2009). According to Ogbe and Egharevba (1992), BVT is a lesser known tropical forest fruit with high consumption but given a less priority in terms of research, production, improvement, storage and hence not domesticated.…”
Section: Introductionmentioning
confidence: 95%
“…According to Ogbe and Egharevba (1992), BVT is a lesser known tropical forest fruit with high consumption but given a less priority in terms of research, production, improvement, storage and hence not domesticated. Efforts made so far to domesticate this crop had been concentrated on improving the germination of the seed through presowing treatments (Aghatise and Egharevba, 1994;Nwaoguala et al, 2007;Nwaoguala and Osaigbovo, 2009) which has been found to exhibit uneven and poor germination due to its thick gelatinous seed coat ). The slow growth of BVT seedlings in the nursery also hampered the domestication of this crop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed coat can be punctured, scarified with sharp sand, excised or removed chemically with concentrated acid. Scarification is recommended in around 7% of tree species, including in the Persian turpentine tree [9], honey locust [10], common myrtle [11], black velvet tamarind [12], black locust [13], lebbeck tree [14], African locust bean [15], Judas tree [16], noni [17], afzelia and African teak [18].…”
Section: Introductionmentioning
confidence: 99%
“…BVT is an important non-timber multipurpose agroforestry crop with a high potential [1]. The potentials of BVT as food supplement, in herbal medicine and as source of energy are well documented [2][3][4]. According to Agbani [5], BVT is a lesser known tropical forest fruit with high consumption but given a less priority in terms of research, production, improvement, storage and hence not domesticated.…”
Section: Introductionmentioning
confidence: 99%